2010
DOI: 10.1186/1471-2458-10-478
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dental erosion and associated risk factors in 12-13-year-old school children in Southern China

Abstract: BackgroundDental erosion has been investigated in developed and developing countries and the prevalence varies considerably in different countries, geographic locations, and age groups. With the lifestyle of the Chinese people changing significantly over the decades, dental erosion has begun to receive more attention. However, the information about dental erosion in China is scarce. The purpose of this study was to explore the prevalence of dental erosion and associated risk factors in 12-13-year-old school ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
74
6
23

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 19 publications
19
74
6
23
Order By: Relevance
“…Various studies have identified consumption of lemon drinks as an important risk indicator for development of dental erosion due to its acidic contents (citric acid) (10,12). The findings of the present study were also in agreement with the findings of previous studies and frequent consumption of lemon drinks was found to be an important risk factor for dental erosion.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Various studies have identified consumption of lemon drinks as an important risk indicator for development of dental erosion due to its acidic contents (citric acid) (10,12). The findings of the present study were also in agreement with the findings of previous studies and frequent consumption of lemon drinks was found to be an important risk factor for dental erosion.…”
Section: Discussionsupporting
confidence: 83%
“…However, it is more worrying when this condition is found in an alarming proportion among children. If this condition is not controlled and stabilized, the child may suffer from severe tooth surface loss, tooth sensitivity, over closure, poor aesthetics, or even dental abscesses in the affected teeth (10). Since, there is not currently enough data to draw conclusions about the prevalence of dental erosion, more studies are needed in order to better understand the epidemiology of this destructive condition.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to record erosive wear in all age groups to gather comprehensive information about the prevalence, distribution and incidence of erosive wear among different ages with possible different dietary habits [11] [12]. Geographic location seems to influence the prevalence rates observed in literature, since cultural, ethnical and dietary habits vary according to the region where the study was conducted [13] [14]. Saudi Arabia is one of several countries who underwent an especially rapid development and modernization with food culture changes in the past decades, through adoption of a more westernized diet in lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…These roles in prevention require the acquisition of numerous cross-disciplinary psychosocial and skill-based competencies ranging from role beliefs and commitment, to collaborative care [16] [17]. A long-standing challenge in dental education is preparing future clinicians to participate in prevention of oral/systemic health issues [14]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…Bu bağlamda özellikle genç erişkinlikler arasında hazır gıdaları ve gazlı içecekleri kullanma alışkanlığı artmıştır. Birçok çalışmaya göre gelişmiş ve gelişmekte olan ülkelerin genç çocuk ve erişkinlerinde dental erozyon prevalansının arttığı gözlenmiştir [31][32][33] . Erozyon toplumun her yaş grubunda görüle-bilen yüksek prevalansa sahip eskiden olduğu gibi günümüzde de devam eden önemli bir diş problemidir.…”
Section: Erozyonun Prevalansiunclassified